STRATEGI PEMBERDAYAAN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN PRODUKSI UMKM - Fitria Astuti; Siti Maryam; Burhanudin AY (JURNAL ILMIAH EDUNOMIKA, 2022)
The purpose of this study is to analyze the strategy of empowering human resources of weaving craftsmen at the center of the goyor sarong industry "advanced companies" in the village of Kenteng Sukoharjo. The population of this study are craftsmen in the weaving section. The population sampled was 40 weaving craftsmen. The data analysis technique used in this research is analytical hierarchy process (AHP) by weighting the value of each criterion which includes the ability to trust leadership and motivation with Expert choice 11. The conclusion of ability and motivation is that it is effective to increase production. An alternative strategy is to monitor / supervise the weaving craftsmen and give rewards to weavers whose work is neat, good and can finish in a short time, can be just a greeting or a bonus.